Performance Evaluation of Single Leg Thermoelectric Module for Different Materials Under Various Operating Conditions - Uglah, Aqeel M.; Saleem, Khalid B.; Sultan, Hussein S.; Kolsi, Lioua (Basrah Journal for Engineering Sciences, 2025)
The thermoelectric behavior of different materials under various conditions has been investigated numerically by using the heat transfer module of the COMSOL Multiphysics software platform. A simulation study of the thermoelectric materials (TEM) performance was created by altering the current applied from 0.1 to 1.0 A and setting the hot side temperature (T H ) as 273 K. The impact of different performance metrics, such as cold side temperature and output voltage, has been proven and investigated. It has been shown that the material of the thermoelectric legs', length of leg, and thickness of electrodes significantly impact the thermal and electrical performance of the thermoelectric (TE) module. Appropriate ranges have been studied in the simulation, such as the amperage values applied to the unit as mentioned above, the length of the leg within a range of 1 to 8 mm, and the thickness of the electrode with different values of 0.1 to 0.5 mm, which will achieve excellent performance for the Thermoelectric unit. Modeling and simulation results demonstrated and revealed the optimal and potential use of bismuth telluride (Bi 2 Te 3 ) as well as lead telluride (PbTe) as suitable for Peltier cooling applications. As for the use of cobalt triantimonide (CoSb 3 ), it is in contrast to the two previous metals, as it is effective and appropriate if applied to power generation. The results are validated with another study from the literature, and there is an excellent agreement with an error rate that does not exceed 0.164%.